Fourth Five Year Plan Government of Uttar Pradesh - Planning Commission (Planning Commission, 1969)
The Himalayan region is mountainous having extensive and thick forests. It comprises Uttar Kashi, Chamoli, Pithoragarh, Tehri Garbwal, Garhwal and Almora Districts, Naini Tal tehsil of Naini Tal District and Chakrata and a part of Dehra Dun tehsil of Dehra Dun District. This region is thinly populated and there are no large towns, though there are a number of beautiful hill stations like Chakrata, Mussoorie, Naini Tal. Ranikhet and Almora. Dehra Dun is the only city with a population of more than one lakh. On account of the stony nature of the land cultivation is possible only in river valleys and terraced hill slopes. The chief crops of the area are rice and wheat. Naini Tal and Almora Districts have some orchards while the sub-mountain area of Dehra Dun produces tea as well.
Planning Department, Government of Uttar Pradesh
Planning Department, Government of Uttar Pradesh